Investigation of alternative molecular approaches for enhanced traceability of illegally traded Temminck's Ground Pangolins (Smutsia temminckii) - Bastos, Armanda D.S. (University of Pretoria, 2025)
Dissertation (MSc (Zoology))--University of Pretoria, 2018.